In vitro Evaluation of Selected Fruit Extracts against Cardiovascular Diseases - Reddy, Dr. P. Dwarakanadha (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: Cardiovascular diseases (CVDs) are the number one cause of death globally, more people die annually from CVDs than from any other cause. Much of this interest centers on the use of antioxidant vitamins and the antioxidant properties of herbal materials, although some herbal materials may also improve conventional cardiovascular risk factors or have antithrombotic effects. This study was undertaken to investigate the in vitro evaluation of selected fruit extracts against cardiovascular metabolic syndrome with methanolic extracts of Schisandra (Magnolia vines), Muntingia calabura, and Alangium salviifolium fruits. Materials and Methods: Angiotensin-converting enzyme (ACE) inhibition assay, assay of nitric oxide (NO) scavenging activity, and in vitro Î±-amylase inhibitory studies were carried out to evaluate the cardiovascular metabolic syndrome activity of methanolic extract of Schisandra (M. vines), M. calabura, and A. salviifolium fruits. Results: The preliminary phytochemical screening showed the presence of various phytoconstituents such as flavonoids, phenolic compounds, triterpenoids, tannins, saponins, amino acids, proteins, and carbohydrates in the fruit extracts. The ACE inhibitory activity of fruit extracts was represented as percentage ACE inhibition. The fruits extract demonstrated ACE inhibitory activity at a concentration of 800 Î¼g/ml, showing an inhibition >50%. Statistically significant results were observed in in vitro Î±-amylase inhibitory assay and in NO scavenging assay. Conclusion: The role of redox mechanisms in the control of expression and activity of rennin-angiotensin system (RAS) enzymes and angiotensin receptors may provide important insight into the function of local tissue RAS in health and disease states. The selected fruit extracts have promising role against CVDs.